2008
DOI: 10.1089/pop.2008.0006
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of an Integrated Population Health Enhancement and Disease Management Program on Employee Health Risk, Health Conditions, and Productivity

Abstract: This study evaluated the impact of an integrated population health enhancement program on employee health risks, health conditions, and productivity. Specifically, we analyzed changes in these measures among a cohort of 543 employees who completed a health risk assessment in both 2003 and 2005. We compared these findings with 2 different sets of employees who were not offered health enhancement programming. We found that the DIRECTV cohort showed a significant reduction in health risks after exposure to the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
56
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 64 publications
(58 citation statements)
references
References 30 publications
0
56
0
1
Order By: Relevance
“…Overall levels of risk to health were significantly reduced, while there was also a significant reduction in the prevalence of depression, although rates of anxiety significantly increased. There were net cost savings from a health-care payer perspective, although the costs of participation in the health promotion programme were not reported (Loeppke et al , 2008). In Canada, an uncontrolled evaluation of a comprehensive workplace health promotion programme, including information for stress management reported a significant reduction in stress levels, signs of stress and feelings of depression at the end of a 3-year study period.…”
Section: Resultsmentioning
confidence: 99%
“…Overall levels of risk to health were significantly reduced, while there was also a significant reduction in the prevalence of depression, although rates of anxiety significantly increased. There were net cost savings from a health-care payer perspective, although the costs of participation in the health promotion programme were not reported (Loeppke et al , 2008). In Canada, an uncontrolled evaluation of a comprehensive workplace health promotion programme, including information for stress management reported a significant reduction in stress levels, signs of stress and feelings of depression at the end of a 3-year study period.…”
Section: Resultsmentioning
confidence: 99%
“…These improvements in lifestyle were also associated with a decline in health care costs, an increase in productivity, and a positive return on investment. Loeppke et al 34 have reported that a worksitebased health enhancement program produced favorable changes that persisted for 3 years. Sternfeld and associates 35 reported on a worksite-based randomized trial designed to improve fruit and vegetable intake and physical activity behaviors using an e-mail program.…”
Section: Optimal Lifestyle and Disease Incidence 291mentioning
confidence: 99%
“…One reported favorable results. 45 Two additional studies, which we considered to have high-quality methods, reported unfavorable results. 46,47 The single favorable study tested a program implemented within one employer across geographically dispersed worksites.…”
Section: Combination Programs: Health Promotion Disease Management mentioning
confidence: 99%